Dynamic methylation and expression of alternative promoters for oestrogen receptor alpha in cell line models of fulvestrant resistance - Juliane Albrecht; Mirjam Müller; Völundur Hafstað; Kamila Kaminska; Johan Vallon‐Christersson; Gabriella Honeth; Helena Persson (Molecular Oncology)
Oestrogen receptor alpha (ER; gene symbol ESR1) is the most important prognostic and treatment‐predictive biomarker in breast cancer. Drugs targeting oestrogen and ER for endocrine therapy of breast cancer include aromatase inhibitors, the selective ER modulator tamoxifen and the selective ER degrader fulvestrant. Tumours can develop resistance to endocrine therapy through several mechanisms, which is often linked to altered expression of ER. To investigate the role of promoter methylation in the regulation of ESR1 expression, we used bisulfite sequencing to measure methylation at CpG sites in alternative ER promoter regions for six cell line models of fulvestrant resistance. Both CpG methylation and expression of alternative first exons changed dynamically, with striking differences between cell lines that had stable or unstable resistance upon fulvestrant withdrawal. Methylation at some CpG sites was strongly negatively correlated with expression of specific first exons. In a breast tumour cohort, higher relative expression of upstream alternative first exons was associated with worse prognosis in post‐menopausal women with ER‐positive tumours who received endocrine therapy.